Konsep CInta Sufi RÈ‚BIâ€™AH AL-â€˜ADAWIYYAH - Fikri Mahzumi (Institut Keislaman Abdullah Faqih Gresik, 2015)
This article is effort to explore the conception of RÈƒbiâ€™ah Al-â€˜Adawiyyah about her spiritual experience on sufism. According to her, love was actualized as â€œal-á¸¥ubb al-ilÃ¢hi and al-khullahâ€. Both terms explain into her poems and idoms these mean a system of love. Therefore she stands out among the early ascetics like a star of Divine love. It must be noted that Rabi'a had not completely built an original system of love to deserve such a title. What she did was to emphasise the importance of disinterested love for God; and this was much needed at her time. She basically divided love on the basis of its motives, that is, whether the love is motivated by self-interest or not. This simple division proved to be very successful: it became a central theme in almost all Sufi books, and inspired individual Sufiâ€™s theories on love. In addition to her contribution to the concept of love, Rabi`a is also important inasmuch as she is one of the original female Sufis emerging in the eighth century. This is important since it shows that Sufism gave women the greatest opportunity to attain the rank of sainthood. As a result, the title of saint was bestowed upon women equally with men.